The roles of some agility performance parameters on the linear, single sprint skills of young male basketball and handball players - Bilge, Murat; Caglar, Emine; Saavedra, Jose Miguel (Progress in Nutrition, 2020)
Study Objectives: This study aimed to examine the roles of some agility parameters on the linear, single sprint skills among young male basketball and handball players. Methods: The participants in this study were male basketball players (BP) (n = 15,  ±SD= 15.30±0.48) and handball players (HP) (n = 32,  ±SD= 16.81±1.63) who trained regularly, and a control group (CG) (n=31,  ±SD= 15.87±0.80). They participated in 0 to 30 m linear speed tests, a T test, a 505 agility test, and an Illinois agility test. Changes in direction, side stepping, reversing direction, and running backward were the main sub-parameters of agility performance that constituted the independent variables. A multiple regression analysis was conducted if these independent variables predicted the 0 to10 m, 10 to 30 m, and 0 to 30 m sprint performances separately. One way ANOVA was performed to determine group differences in all the independent variables. Results: The ANOVA revealed statistically significant differences between groups for the independent variables (p